ANALISIS TINDAK TUTUR DIREKTIF TOKOH JIRO HORIKOSHI DALAM FILM KAZE TACHINU - Gede Eka Dana Artama; Ladycia Sundayra (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
This research aims to investigate the meaning of directive speech acts uttered by the character Jiro Horikoshi and describe the responses of interlocutors to the utterances made by the character Jiro Horikoshi in the film